SLEEP APNEA: MANIFESTATION OR CAUSE OF SEIZURES IN CHILDREN? CASE REPORT - Tamara-Marcela Marcovici; Oana Belei; Daniela Chiru; Ramona Stroescu; Giorgiana Brad; Laura Olariu; Otilia Marginean (Amaltea Medical Publishing House, 2014)
Introduction. Sleep apnea (SA) in children is underdiagnosed. Compromising somatic development and alterated quality of life are frequently present. Central sleep apnea (CSA) may be the cause of convulsive episodes in sleep or could be their result. Polysomnography is the gold-standard of SA objective assessment. Material and methods. We present a 7-year-old boy hospitalized in September 2013 for choking episodes occurred during sleep. The assessment was made by history, clinical examination, laboratory investigations (functional, imaging, biological) and interdisciplinary checkups. Results. Repeated respiratory tract infection and a history of about 20 days of episodes of choking were established by anamnesis. Were diagnosed: underweight status; chronic rhinitis; tonsillar hypertrophy; obstructive ventilatory dysfunction; mixed sleep apnea with predominant central component; atopic status; convulsions. Imaging explorations revealed normal aspects. Complex hygienic-dietary and medical treatment has led to the disappearance of respiratory disorders during sleep, with normalization of spirometric parameters and nutritional status. Conclusions. Polygraphic sleep study identifi ed sleep apnea, indicating the predominance of the central component and facilitating etiologic diagnosis. Interdisciplinary management led to favorable evolution of the case.